ممارسة المستهلك لحق العدول: بين الاطلاق والتقييد - بوشول, عبد الغني; ربحي تبوب ., فاطمة الزهراء (University of Eloued جامعة الوادي, 2022)
عدول هو حق المستهلك في التراجع عن العقد الذي أبرمه، ومنح المستهلك الحق في ممارسة العدول يجد مبرره في كونه الطرف الضعيف في العلاقة التعاقدية في مواجهة المهني، وكذا الوسائل التي يستعملها هذا الأخير للترويج لمنتجاته وما قد تسببه من تضليل للمستهلك، حيث يمارسه هذا الأخير دون وجه سبب، كونه متعلق بالنظام العام، وهو حق خاضع للسلطة الكاملة والتقديرية للمستهلك في ممارسته، وبدون مقابل، وإن كان ممارسة حق العدول منحه المشرع للمستهلك حصراً، إلا أنه قيده بمدّة زمنية محدودة من أجل الحفاظ على استقرار المعاملات، واختلفت التشريعات حول مقدار هده المدّة، حيث أنها تتراوح في مجملها بين السبعة أيام والثلاثون يوماً، وذلك بحسب ظروف كل مشرع وكذا طبيعة محل العقد، كما أن التشريعات اقتصرت هذا الحق على بعض العقود التي يرى فيها حاجة المستهلك للتروي والتدبر والتأني. الكلمات المفتاحية: حق العدول؛ المستهلك؛ المهني؛ الطرف الضعيف؛ عقد الاستهلاك. Retraction is the consumer’s right to withdraw from the contract he concluded, and granting the consumer the right to practice retraction finds its justification in being the weak party in the contractual relationship in the face of the professional, as well as the means used by the professional to promote his products and what may cause misleading to the consumer, as the latter practices it as it is related to public order. It is a right subject to the full and discretionary authority of the consumer to exercise it without compensation, although the exercise of this right was granted by the legislator exclusively to the consumer, but he restricted it for a limited period of time in order to maintain the stability of transactions. Legislations differed about the amount of this period, as it ranges in total between seven and thirty days, depending on the circumstances of each legislator as well as the nature of the subject of the contract. Legislation has limited this right to some contracts in which the consumer sees the need for deliberation and reflection. key words: Right of retraction; Consumer; Professional; weak side in contract; consumption contrac
المجلد13 العدد2
Keywords: حق العدول ; المستهلك ; المهني ; الطرف الضعيف ; عقد الاستهلاك; Right of retraction ; Consumer ; Professional ; weak side in contract ; consumption contract